THE SUCCESSFUL FACTORS TREATMENT OF MB TYPE LEPROSY IN THE WORKING AREA OF JENU PUBLIC HEALTH CENTER, TUBAN REGENCY - vivin Nor Zahro; Teresia Retna; Yasin Wahyurianto (Universitas Islam Balitar, 2023)
Leprosy is a chronic infection caused by Mycobacterium leprae which if not treatedimmediately will become progressive. The government has a treatment success target of >90%,but in some areas the effort to eradicate leprosy type MB is still slow [1]. The purpose of this studywas to determine the success factors for the treatment of MB type leprosy in the working area ofthe Jenu Public Health Center, Tuban Regency.The research design used was descriptive, cross sectional time approach. The populationis all patients with leprosy who seek treatment in the working area of the Jenu Public Health Centerfor a cohort period of 76 months (January 2016-April 2022) as many as 35 people, the samplingtechnique used is total sampling. Research instruments in the form of questionnaires andobservation sheetsThe results of the study were obtained from 35 patients with MB type leprosy almostentirely (82.9%) were found without disability, all (100%) immediately received treatment, all(100%) received good family support, all (100%) the role of health workers was good.The success of treatment for leprosy type MB requires support from the family and thesurrounding community, the family is the closest person who can supervise and control thepatient's condition. Treatment of leprosy also requires the role of health workers because healthworkers can provide encouragement to patients, in addition, if the patient has not taken themedicine, the health worker will come to give the medicine. Efforts to find and treat patients withMB type leprosy are very important, for this reason, family and community support are needed sothat there is no feeling of shame and immediately comes to the nearest health servic